Apolipoproteins AI, AII, and CI stimulate placental lactogen release from human placental tissue. A novel action of high density lipoprotein apolipoproteins. - Handwerger, S (1987)
High density lipoproteins (HDL) stimulated a dose-dependent increase in the release of placental lactogen (hPL) from human placental explants. The stimulation was not prevented by delipidation of HDL but was completely blocked by tryptic digestion. Delipidated apolipoproteins (Apo) AI, AII, and CI also stimulated hPL release but other apolipoproteins were without effect. HDL and Apo CI had no effects on the release of luteinizing hormone and follicle-stimulating hormone from rat pituitary cells or the release of prolactin from human decidual cells. Because placental cells have specific HDL receptors and plasma HDL concentrations increase during pregnancy, these results strongly suggest a role for HDL in the regulation of hPL release during pregnancy possibly independent of their usual role in plasma lipid transport.